PEMANFAATAN DAUN SIRSAK (Annona muricata L.) SEBAGAI FEED ADDITIVE TERHADAP KONSUMSI PAKAN, PBB, FCR DAN LEMAK ABDOMINAL PADA AYAM BROILER - Muhammad Zahid Al Fajar; Oskar Induk; Roosena Yusuf (Universitas Mulawarman, 2019)
The purpose of this research was to determine the productivity performance of broiler chickens given soursop leaf flour. The design used in this study was Completely Randomized Design (CRD) with 100 DOCs consisting of 5 treatments and 5 replications with each replication consisting of 4 chicken, namely P0 = control; P1 = soursop leaf flour 10g/kg feed; P2 = soursop leaf flour 20g/kg feed; P3 = soursop leaf flour 30g/kg of feed; P4 = soursop leaf flour 40g/kg of feed. The total number of broilers used in this research was 100. The results of analysis of variance showed that the addition of soursop leaf flour in feed did not have a significant effect (F<0.05) on feed consumption in broiler chickens. In addition, the results obtained from the administration of soursop leaves in 3 parameters and their interactions had a significant effect (P>0.05) on body weight gain, feed conversion and abdominal fat.